Personal Income and Substance Use among Emerging Adults in the United States - Kar, Indra Neal (Subst Use Misuse, 2018)
BACKGROUND: Taxation and other policy measures have been implemented across the United States to curb the accessibility of substance use, especially among youth. While the inverse relationship between price and youth consumption is well known, available research on youth earned income and substance use is sparser, particularly among emerging adults. OBJECTIVES: We examined the association between emerging adult past-year personal income and 30-day substance use. METHODS: We analyzed data from Wave 5 (n = 2,202) of the NEXT Generation Health Study, an annual survey study administered to a nationally representative sample of emerging adults in the U.S. Wave 5 (mean age=20.28 years, SE=0.02 years) was administered during the 2013–2014 academic year. After grouping participants into five levels of self-reported, pre-tax personal income, we used binomial logistic regression to examine the association between personal income and cigarette smoking, marijuana use, alcohol use, and heavy episodic drinking (HED). RESULTS: In unadjusted models, those at certain levels of higher past-year income were more likely to smoke cigarettes, consume alcohol, or engage in HED at least once in the past 30 days. Several associations remained significant after controlling for covariates. Most associations were no longer significant after including perceived peer norms as additional covariates. Personal income was not associated with 30-day marijuana use in unadjusted or adjusted models. CONCLUSIONS/IMPORTANCE: Higher earned income may provide emerging adults greater economic access to cigarettes and alcohol, but the association might be partly attenuated by social factors, particularly perceived peer norms.